Epidemiology of cervical cancer in the pre- and post-pandemic period of COVID-19, in the State of Pará (Research, Society and Development, 2024)
Cervical cancer is considered a serious public health problem, being the second most common cause of cancer among women, caused mainly by infection with the Human Papillomavirus. With the advent of the COVID-19 pandemic, as well as restrictive measures such as social isolation, there was a change in screening for the disease. Thus, this study aimed to analyze the epidemiological scenario of cervical cancer in the State of Pará between the years 2017 and 2022. This is a cross-sectional study with a descriptive type and quantitative approach carried out in the State of Pará where information was extracted on cervical cancer screening of adult women, contained in the Information Technology Department of the Unified Health System from 2017 to 2022. The scientific research was sociodemographic and clinical-epidemiological. It can be observed that during the pandemic period it had an impact on notifications, reducing the occurrence of PCCU by 47.69%, attributing it to social isolation and fear of contamination by SARS-COV-2. Among the regions with the highest frequency of PCCU is Belém, followed by Barcarena, to the detriment of women's health education campaigns. In relation to the alterations with the highest recorded incidences, squamous cell atypia of undetermined significance was found, with 41.07%, followed by low-grade intraepithelial lesions, 35.35%. It is therefore inferred that the COVID-19 pandemic corroborated the implementation of the PCCU. In this way, the importance of tracking and vaccination as prevention tools, combined with health education as ways to mitigate this injury, stands out.